Caesarean section and neonatal survival and neurodevelopmental impairments in preterm singleton neonates. Issue 2 (22nd April 2019) - Lodha, Abhay; Ediger, Krystyna; Creighton, Dianne; Tang, Selphee; Lodha, Arijit; Wood, Stephen
Abstract: Introduction: Evidence is lacking regarding the benefit of caesarean section (CS) for long-term neurodevelopmental outcomes in singleton preterm neonates. Therefore, uncertainty remains regarding obstetrical best practice in the delivery of premature neonates. Objective: Our objective was to determine the association between the mode of delivery and neurodevelopmental outcomes in preterm singleton neonates who were delivered by vaginal route (VR), CS with labour (CS-L), or CS without labour (CS-NL). Methods: Singleton neonates of less than 29 weeks' gestation born January 1995 through December 2010 and admitted to our NICU and then assessed at neonatal follow-up clinic were studied. The primary outcome was neurodevelopmental impairment (NDI) defined as cerebral palsy, cognitive delay, major or minor visual impairment, or hearing impairment or deafness at 36 months' corrected age. Results: In this retrospective cohort study of 1, 452 neonates, 1, 000 were eligible for the study and 881 (88.1%) were available for follow-up. There was no significant difference in mortality between VR group, CS-L group, and CS-NL group. At 3 years, there was no significant difference between the three groups in terms of NDI. The odds of composite outcome of mortality or NDI for neonates born via CS-NL versus VR, and CS–L versus VR were 0.90 (95% confidence interval [CI]: 0.59 to 1.37) and 1.08 (95% CI: 0.72 to 1.61), respectively. Propensity score-based matched-pair analyses did not show a significant association between the composite outcome and CS with or without labour. Conclusions: CS was not associated with increased survival or decreased risk of NDI in premature singleton neonates born at less than 29 weeks' gestation.